A Quasi-Experimental Study of a Community-Based Training Program to Reduce Death-Related Existential Anxiety Among Rural Elderly Women in Nineveh, Iraq - Shireen Mousa; Iman Mustafa (RaSAIL Media Group, Semarang, Indonesia, 2026)
Existential anxiety related to death can be a significant psychological problem among older adults, especially women living in rural settings where access to mental health support may be limited. The study examined the potential effectiveness of community-based training programs in reducing existential anxiety related to death among elderly women in rural Nineveh, Iraq. A quasi-experimental pre-test/post-test design with an unequal control group was used. The study involved 25 women aged 60-70 years, selected through purposive sampling, with 14 assigned to the intervention group and 11 to the control group. The intervention consisted of 10 sessions delivered over two weeks. Outcome assessments were conducted using the 36-item Existential Death Anxiety Scale developed by the researchers for this population. The intervention group showed a much greater decrease in anxiety scores than the control group (mean reduction = 38.64 vs. 4.18; t = 9.83, p < 0.05), and in-group analysis also showed a significant pre-post reduction in the intervention group (pre-test mean = 142.86; post-test mean = 104.22; t = 11.59, p < 0.05). These findings suggest that the program may help reduce existential anxiety related to death among rural elderly women. However, the results should be interpreted with caution due to the small, non-random sample, the use of geographically separated groups, and the absence of follow-up assessments. Larger, more rigorous studies are needed to confirm the effectiveness and long-term impact of interventions.